Host cell interactome of tyrosine-phosphorylated bacterial proteins. - Selbach, Matthias; Paul, Florian Ernst; Brandt, Sabine; Guye, Patrick; Daumke, Oliver; Backert, Steffen; Dehio, Christoph; Mann, Matthias (Cell Host & Microbe, 2009)
Selective interactions between tyrosine-phosphorylated proteins and their cognate, SH2-domain containing ligands play key roles in mammalian signal transduction. Several bacterial pathogens use secretion systems to inject tyrosine kinase substrates into host cells. Upon phosphorylation, these effector proteins recruit cellular binding partners to manipulate host cell functions. So far, only a few interaction partners have been identified. Here we report the results of a proteomic screen to systematically identify binding partners of all known tyrosine-phosphorylated bacterial effectors by high-resolution mass spectrometry. We identified 39 host interactions, all mediated by SH2 domains, including four of the five already known interaction partners. Individual phosphorylation sites recruited a surprisingly high number of cellular interaction partners suggesting that individual phosphorylation sites can interfere with multiple cellular signaling pathways. Collectively, our results indicate that tyrosine-phosphorylation sites of bacterial effector proteins have evolved as versatile interaction modules that can recruit a rich repertoire of cellular SH2 domains.